2016
DOI: 10.1089/thy.2015.0640
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life Priorities in Patients with Thyroid Cancer: A Multinational European Organisation for Research and Treatment of Cancer Phase I Study

Abstract: Thyroid cancer patients cross-culturally rate fatigue-related issues as highly important for their QoL, calling for increased efforts to find successful treatments for this problem. Vocational rehabilitation is also highly relevant for them and should therefore be an important aim of multidisciplinary care. The third important area of concern is psychological issues, especially fear of progression and of additional treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 51 publications
1
47
0
2
Order By: Relevance
“…The second aim was to shorten the module without compromising its comprehensiveness. The patient responses confirmed that the QoL issues identified in phase I of this module development (Singer et al 2016) are relevant and important to patients. Most of the items were well accepted by the patients.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The second aim was to shorten the module without compromising its comprehensiveness. The patient responses confirmed that the QoL issues identified in phase I of this module development (Singer et al 2016) are relevant and important to patients. Most of the items were well accepted by the patients.…”
Section: Discussionsupporting
confidence: 58%
“…The European Organisation for Research and Treatment of Cancer (EORTC) therefore created a thyroid-cancer-specific module to be used as a supplement of the quality-of-life core questionnaire EORTC QLQ-C30 (phase I and II of the EORTC module development process (Johnson et al 2011)). This (provisional) module was developed based on two systematic reviews and structured interviews with 110 patients and 57 health care professionals (Singer et al 2016). In these previous phases, items were derived from a longer list of QoL issues that could be relevant for thyroid cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms can be caused by the disease itself or by treatment-related side effects. The symptom burden exerts a significant impact on the quality of life and is highly prioritised by patients with thyroid cancer 27 . A problem-solving approach in the management of symptom problems is generally recommended 28 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the personal experience of this first author, issues related to thyroid diseases and thyroid surgery are rarely discussed in either undergraduate or graduate level courses in speech-language pathology. Therefore, the need for continuing education in thyroid disease and treatment, and increased awareness of a multidisciplinary approach to treatment is essential for all associated healthcare professionals and would be highly beneficial to these patients (6,77).…”
Section: Discussionmentioning
confidence: 99%